REVOLUTIONIZING ORGANIZATIONAL EFFICIENCY WITH DIGITAL TRANSFORMATIONAL LEADERSHIP: THE BRIDGING ROLE OF EMPLOYEE PERFORMANCE AND ENGAGEMENT - Mariana (Feedforward: Journal of Human Resource, 2025)
This study investigates the influence of digital transformational leadership on organizational efficiency, focusing on the mediating effects of employee performance and work engagement. In an increasingly digitalized business environment, leaders must leverage technology to guide their teams toward enhanced productivity, innovation, and agility. However, only some studies have comprehensively examined the intersection of digital leadership behaviors, employee- related factors, and efficiency metrics. Adopting an exploratory approach, this paper synthesizes recent literature (2018–2023) from Scopus-indexed journals to identify patterns and gaps in the current understanding of how digital transformational leadership can foster a high-performing, engaged workforce that drives improved organizational efficiency. The review involved searching key terms such as "Digital transformational leadership," "Employee performance," "Work engagement," and "Organizational efficiency," ensuring a targeted examination of relevant sources. This integrative approach supports a comprehensive perspective. The findings suggest that digital transformational leadership behaviors—such as providing a clear digital vision, encouraging innovation, and using collaborative platforms— positively affect employee performance and work engagement. This, in turn, enhances organizational efficiency by optimizing resource use, improving workflow processes, and fostering a more innovative and responsive organizational culture. The results also highlight the importance of managerial capabilities in navigating digital transformation initiatives. However, the paper acknowledges certain limitations, including its reliance on secondary data and the exploratory nature of its design. Future empirical studies should further validate these relationships, considering contextual factors and longitudinal frameworks to strengthen generalizability and applicability.